2020
DOI: 10.1164/rccm.202003-0821oc
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19–related Genes in Sputum Cells in Asthma. Relationship to Demographic Features and Corticosteroids

Abstract: Background: Coronavirus disease 2019 is caused by SARS-coronavirus 2 (SARS-CoV-2). Angiotensin converting enzyme 2 (ACE2) and transmembrane protease serine 2 (TMPRSS2) mediate viral infection of host cells. We reasoned that differences in ACE2 or TMPRSS2 gene expression in sputum cells among asthma patients may identify subgroups at risk for COVID19 morbidity. Methods:We analyzed gene expression for ACE2 and TMPRSS2, and for intercellular adhesion molecule 1 (ICAM-1)(rhinovirus receptor as a comparator), in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
403
2
18

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 414 publications
(453 citation statements)
references
References 24 publications
19
403
2
18
Order By: Relevance
“…There were no significant differences between these groups in terms of age, disease severity, smoking status or other comorbidities known to affect ACE2 expression and/or associated with increased risk of COVID-19 ( Table 1). Sputum cell ACE2 mRNA expression was detectable in 22/36 COPD subjects (61.1%) and, consistent with prior observations in asthma (17), significantly reduced in ICS users compared to nonusers (Fig 1a). Sputum cell expression of the serine protease TMPRSS2 that is used by SARS-CoV-2 for mucosal entry (13) was detectable in all subjects with no significant difference observed between ICS users and non-users (Fig 1b).…”
Section: Ace2 Mrna Expression Is Reduced In Copd Patients Taking Inhasupporting
confidence: 91%
See 3 more Smart Citations
“…There were no significant differences between these groups in terms of age, disease severity, smoking status or other comorbidities known to affect ACE2 expression and/or associated with increased risk of COVID-19 ( Table 1). Sputum cell ACE2 mRNA expression was detectable in 22/36 COPD subjects (61.1%) and, consistent with prior observations in asthma (17), significantly reduced in ICS users compared to nonusers (Fig 1a). Sputum cell expression of the serine protease TMPRSS2 that is used by SARS-CoV-2 for mucosal entry (13) was detectable in all subjects with no significant difference observed between ICS users and non-users (Fig 1b).…”
Section: Ace2 Mrna Expression Is Reduced In Copd Patients Taking Inhasupporting
confidence: 91%
“…ACE2 is expressed primarily in the nasal goblet cells and type II pneumocytes within the respiratory tract (30) and is upregulated in subject groups known to be associated with increased disease severity including elderly individuals (31) and patients with diabetes (17), indicating that it may play a clinically important role in governing susceptibility to virus acquisition and/or development of severe disease in at-risk groups. ACE2 expression has similarly been shown to be increased in COPD: using combined transcriptomic and immunohistochemical analyses, Leung et al recently demonstrated that epithelial ACE2 expression is increased in bronchial brushings/tissue samples from COPD subjects versus healthy controls (32), effects also previously shown in cigarette smoke exposure animal models (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of Betamehasone and Dexamehasone effect on hinge site blockage not been explored, the two corticosteroids have the same molecular weight and high structural similarity (the only difference is the orientation of the methyl group on carbon 16) so which could have similar effects. Use of inhaled corticosteroids had been associated with lower expression of ACE2 and TMPRSS2, but treatment with Triamcinolone Acetonide did not decrease expression of either gene [19]. On the other hand, the use of Atazanavir (protease inhibitor) has been reported in computer studies with inhibitory potency activity with Kd of 94.94 nM against the SARS-CoV-2 3C-like protease inhibitor [2].…”
Section: Discussionmentioning
confidence: 99%